Answer:
Expression: 1 ⇒ 18 + 63 f
Expression: 2 ⇒ 25
Step-by-step explanation:
* Lets revise at first the order of operations
- The order of these operations is:
# Parenthesis
# Exponents
# Multiplication and Division which comes first from left to right
# Addition and Subtraction which comes first from left to right
- There is a word made from the first letter of each operation
PEMDAS to remember the order of operations
* Lets solve the problem
# Expression: 1
∵ 9(2 + 7 f)
- To simplify this expression multiply the bracket by 9
∵ 9(2 + 7 f) = 9 × 2 + 7 f × 9
∵ 9 × 2 = 18
∵ 7 f × 9 = 63 f
∴ 9(2 + 7 f) = 18 + 63 f
* Expression: 1 ⇒ 18 + 63 f
# Expression: 2
∵ 6 × 7 - 3² × 9 + 4³
- At first simplify exponent
∵ 3² = 9 and 4³ = 64
∴ 6 × 7 - 3² × 9 + 4³ = 6 × 7 - 9 × 9 + 64
- Solve the multiplication first
∵ 6 × 7 = 42
∵ 9 × 9 = 81
∴ 6 × 7 - 3² × 9 + 4³ = 42 - 81 + 64
- Solve 42 - 81 first because it comes first from left to right
∵ 42 - 81 = - 39
∴ 6 × 7 - 3² × 9 + 4³ = - 39 + 64
- Add them
∵ - 39 + 64 = 25
∴ 6 × 7 - 3² × 9 + 4³ = 25
* Expression: 2 ⇒ 25